2022
DOI: 10.3857/roj.2021.01025
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated radiotherapy for early stage glottic cancer: efficacy of 3.5 Gy per fraction

Abstract: Purpose: The purpose of this study was to evaluate the treatment outcomes and toxicity profile of patients with early glottic cancer who underwent hypofractionated radiation therapy (RT) with 3.5 Gy per fraction.Materials and Methods: A retrospective review was performed of the medical records of 35 patients with early stage (T1-2N0M0) glottic cancer who underwent definitive RT. The dose fractionation scheme was 59.5 Gy in 17 fractions. Posterior commissure was excluded from the clinical target volume (CTV) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…HFRT with single-fraction doses greater than 2.4 Gy is still experimentally used for H&N cancers, with the exception of early-stage glottic cancer, but its adoption is limited by a lack of high-quality evidence and concerns about potential long-term late toxicity. In early glottic cancer, several published studies have demonstrated the effectiveness of HFRT at doses above 2.4 Gy [9][10][11]. Clinical trials applying stereotactic RT to this cancer are also underway; however, concerns regarding toxicity persist [12][13][14].…”
Section: Editorial Pissn 2234-1900 • Eissn 2234-3156mentioning
confidence: 99%
“…HFRT with single-fraction doses greater than 2.4 Gy is still experimentally used for H&N cancers, with the exception of early-stage glottic cancer, but its adoption is limited by a lack of high-quality evidence and concerns about potential long-term late toxicity. In early glottic cancer, several published studies have demonstrated the effectiveness of HFRT at doses above 2.4 Gy [9][10][11]. Clinical trials applying stereotactic RT to this cancer are also underway; however, concerns regarding toxicity persist [12][13][14].…”
Section: Editorial Pissn 2234-1900 • Eissn 2234-3156mentioning
confidence: 99%
“…In the last 10 years the technical developments have remarkably increased the precision in RT treatment planning and RT delivery (Intensity Modulated RT-IMRT, Image Guided RT-IGRT, Tomotherapy) and have allowed radiation oncologists to use another type of altered fractionation called "hypofractiona¬tion" which employs daily dose (per fraction) of higher than 2 Gy, for instance 2.2-2.75 Gy or even higher [16,17]. All clinical trials and retrospective studies agree that tumor control is at least equivalent to standard fractionation and the post-radiation effects are rather reduced [18][19][20][21][22], let alone the favorable consequences of the lower number of RT fractions (see previous paragraph).…”
Section: Radiobiological Considerationsmentioning
confidence: 99%